Improving IPAS Learning Outcomes through the NHT Cooperative Learning Model Assisted by Wordwall - Dermawan, Deden Dicky; Nisya, Khoirun (Journal of Multidiscipline and Collaboration Research, 2025)
This study aims to improve science and social studies (IPAS) learning outcomes through the implementation of the Numbered Heads Together (NHT) cooperative learning model assisted by Wordwall media for fifth-grade students at SD Negeri Cipanjar Kabupaten Sumedang. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 20 fifth-grade students. Data were collected through teacher and student observation sheets as well as learning achievement tests administered at the end of each cycle. The results showed significant improvements in all observed aspects. Teacher performance increased from 57.5% (poor category) in cycle I to 70% (fair category) in cycle II. Student activity improved from 45% (very poor category) in cycle I to 75% (good category) in cycle II. Students’ mastery learning also increased from 45% in cycle I to 75% in cycle II. Thus, the application of the NHT cooperative model assisted by Wordwall was proven effective in enhancing both student engagement and IPAS learning outcomes. This study implies that teachers can utilize a combination of cooperative learning strategies and interactive digital media to create more meaningful and engaging learning experiences.